Nilai-Nilai Spiritual Sufistik Qasidah Burdah dalam Meningkatkan Religiusitas - Solikin, Asep (Anterior Jurnal, 2015)
In the perspective of the development of one's religiosity can be developed through touches the other side that can bring spiritual and inner shades religious person. It can be touched by some form. The forms that try to offer in this study is about Qasidah Burdah (QB) developed at boarding school and in some majlistaklim in public life can be categorized as an internalization of values in the media application using music as a medium. Researchers used a qualitative approach in this research to complete the study. Researchers believe using this approach because the problem in this study is very holistic, complex, dynamic and full of meaning that is not possible data on the social situation captured by quantitative research methods such as test instrument. Moreover, the authors intend to understand the social situation in depth, find the strategy pattern, hypotheses and theories associated with this research study. The content of the values of Sufism in Qasidah Burdah still have suitability (relevance) to the teachings of Islam in terms of both goals (for the human form in order to be a perfect human being (insan kamil) as a servant of God and as a vicegerent on earth) and material (faith, Sharia and morals). Therefore, Qasidah Burdah can be used as a reference or references in the individual maturation process, especially in Indonesia.